Argument for Prompt Corneal Cross-Linking on Diagnosis of Keratoconus in a Pediatric Patient. Issue 12 (24th December 2022) - Henriquez, Maria A.
Abstract : Abstract: Strong evidence suggests that corneal crosslinking is a safe procedure capable of stopping or slowing down the progression of keratoconus, avoiding visual loss associated with progression, and delaying or preventing the need for corneal transplantation. The progressive and chronic nature of the disease makes the option for prompt crosslinking upon keratoconus diagnosis in a pediatric patient valid.